ANEMIA SEL SABIT - Gede Agus Suwiryawan; I Wayan Putu Sutirta Yasa; DAP Rasmika Dewi (Universitas Udayana, 2013)
Anemia is a form of blood disorder most often occurs in the community. Sickle cell anemia is anemia due to hemoglobinopathy caused by a change in the amino acid-6 of the ? globin chain. Sickle cell anemia is common in tropical areas of Africa and some parts of the region Saudi Arabia, India and the Mediterranean as well as black people in America. In addition there are also careers in various European countries. In pathophysiology, there are amino acid change from glutamic acid to valine in the ?-globin chain that causes red blood cells become sickle-shaped when deoxygenatied, but still be able to return to its normal shape when experiencing oxygenation. When the red blood cell membrane have been amended, the polymerization of red blood cells has become irreversible. Clinical picture seen in sickle cell anemia can be divided into two, namely: acute and chronic. Diagnosis can be done is to distinguish between heterozygous or homozygous sickle cell. Treatment provided in accordance with the clinical picture appears. Treatment that can be done is by blood transfusion, bone marrow transplant, anti-sickling drug delivery, and drug delivery to trigger the synthesis of HbF. Treatment still in the development stage is to use stem cells.